Association of clinic type with receipt of neoadjuvant therapy among patients with localized pancreatic cancer: Value of multidisciplinary clinic. Issue 28 (1st October 2022) - Pathak, Priya; Hacker-Prietz, Amy; Herman, Joseph M.; Zheng, Lei; He, Jin; Narang, Amol
Abstract : 63 Background: Patients with localized pancreatic adenocarcinoma (PDAC) generally benefit from multi-modality therapy, which may be best coordinated through a pancreas multi-disciplinary clinic (PMDC). Whether treatment practice patterns vary based on whether a patient was seen through PMDC versus individual specialty-specific clinics is unclear. Methods: Using institutional Pancreatic Cancer Registry, we identified patients who came to Johns Hopkins Hospital through either PMDC or one of the individual surgical, medical, or radiation oncology clinics for localized PDAC between 2018-2020 and eventually underwent resection. During this time, it was standard practice for borderline resectable (BRPC) patients to undergo at least 4 months of neoadjuvant chemotherapy, with or without radiation, before transitioning to exploration, while locally advanced (LAPC) patients were treated with 4-6 months of chemotherapy, followed by radiation, followed by potential exploration. The primary outcome was completion of neoadjuvant therapy as per the above stage-specific institutional standards. Multivariable analyses were performed to find association between PMDC visit and completion of neoadjuvant therapy, controlling for age, sex, race, stage, baseline performance status and type of chemotherapy. Results: A total of 240 patients met inclusion criteria. Of these, 157 (65.4%) had PMDC visits. Distribution of stage across the cohort included 81 (34.3%), 91 (38.5%), and 64 (27.1%) patients with resectable PDAC, BRPC and LAPC, respectively. Patients in the PMDC group received radiation therapy more commonly (59.7% vs 34.9%, p = 0.004), as compared to patients seen through individual specialty-specific clinics. Mean duration of chemotherapy was higher for patients seen through PMDC (4.4 (SD: 1.7) vs 3.9 (SD: 2.0) months) compared with individual clinics. Completion of neoadjuvant therapy per institutional stage-specific standards was seen in 46% (n = 24) of the patients visiting individual specialty-specific clinics compared to 71% (n = 85) of patients who were seen through PMDC (p = 0.002). The adjusted odds ratio of completion of neoadjuvant therapy per institutional standards for patients seen through PMDC visit was 3.35 times the odds for patients seen through individual clinics (95% CIs 1.46-7.07; p = 0.004). Of note, a higher proportion of patients who were seen through PMDC enrolled in a clinical trial (n = 26, 16.6%) compared with patients seen through individual clinics (n = 6; 7.2%) (p = 0.043). Conclusions: Provision of care through a multi-disciplinary clinic was associated with significantly higher odds of completing neoadjuvant therapy per institutional standards as compared to care through individual specialty-specific clinics. In addition, care through a PMDC may also be associated with increased trial enrollment.